Word boundaries and Fo patterns in Advanced Standard Copenhagen Danish - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1979)
In a previous analysis word boundaries have been denied any influence upon the course of fundamental frequency in the stress groups of Advanced Standard Copenhagen Danish. A small experiment has been carried out, which supports this contention, but which also suggests that in more conservative standards, word boundaries do affect Fo patterns.